Analisa Semiotik Makna Motivasi Lirik Lagu “Cerita Tentang Gunung Dan Laut” Karya Payung Teduh - Syarif Fitri (Jurnal Komunikasi, 2017)
This research entitled Semiotic Analysis Meaning Motivation Song Lyrics "Stories About Mountains and Seas" Work Payung Teduh. This research is intended to know the meaning of the content of the song lyrics. The theory used and relevant in this research is Ferdinand De Sausurre Semiotics Theory. The method used in this study using qualitative methods. The subject of this research is the song lyrics of Stories About the Mountain and the Sea. Techniques Data collection is done by doing the object appreciate research, dissect the object ofresearch and interpret the meaning of signs. This study found some conclusions of meaning that exist in the lyrics of the song About the Mountain and the Sea Work Payung Teduh has the meaning of members of the motivation in the life of each stanza. In each stanza in this song using parable words that can be analyzed in semiotics.Keywords: semiotics, song lyrics, motivation